Developing a Comprehensive Model of Psychological Factors Affecting Audit Quality in the Iranian Auditors’ Community Based on the Grounded Theory Approach - Bizar, Keramat; Naslmosavi, Seyedhossein; Ramezani, Aliakbar (Management Strategies and Engineering Sciences, 2025)
The purpose of this study is to develop a comprehensive model of psychological factors affecting audit quality in the Iranian auditors' community based on the grounded theory approach. The research is fundamental in terms of its objective and exploratory in nature. For data collection, a semi-structured in-depth interview approach was considered alongside library studies. This study, utilizing a qualitative approach and grounded theory methodology, aims to develop a comprehensive model of psychological factors influencing audit quality in the auditors' community. The statistical population of this research consisted of experts, specialists, and university professors in the field of auditing. Purposeful and snowball sampling methods were used to identify experts, and interviews were conducted with 10 experts based on data saturation. In the next step, 71 initial conceptual propositions were derived from open coding, 26 categorical propositions from axial coding, and 4 main categories from selective coding. According to the research findings, based on qualitative data, the psychological factors influencing audit quality can be categorized into four main groups: individual factors, interpersonal factors, environmental and organizational factors, and cognitive and decision-making factors. The study demonstrated that the impact of these factors on audit quality is both direct and indirect, and their interaction can either enhance or diminish audit quality. Identifying, understanding, and properly managing these factors help organizations and auditors improve their performance and enhance audit quality.